1988
DOI: 10.1111/j.1365-2141.1988.tb07605.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in size, shape and osmotic behaviour of red cells after splenectomy: a study of their age dependence

Abstract: In whole blood from splenectomized subjects (n = 20), red cells showed a significant increase of mean surface area (MSA), mean cell volume (MCV), MSA/MCV-ratio and osmotic resistance, with the mean cell haemoglobin concentration (MCHC) being decreased. Studies on red cell populations of different cell age revealed that the increase of MSA affects younger and older cells, whereas the increase of MCV can mainly be ascribed to young cells with low density. The increased osmotic resistance is mainly determined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
(12 reference statements)
1
11
0
Order By: Relevance
“…In older erythrocytes absolute increases of HbA1c and HbA1e2 are measured. Also, an increase in total hemoglobin content and an increase in surface area relative to those of control old cells could be demonstrated [33,34]. Taken together, these observations point towards the retention of vesicles especially in erythrocytes containing older hemoglobin.…”
Section: The Role Of Vesiculation During Erythrocyte Agingsupporting
confidence: 62%
“…In older erythrocytes absolute increases of HbA1c and HbA1e2 are measured. Also, an increase in total hemoglobin content and an increase in surface area relative to those of control old cells could be demonstrated [33,34]. Taken together, these observations point towards the retention of vesicles especially in erythrocytes containing older hemoglobin.…”
Section: The Role Of Vesiculation During Erythrocyte Agingsupporting
confidence: 62%
“…24 25 Another possible use of this flow cytometry technique is the assessment of the evolution of the RBC shape after splenectomy. 26 Using flow cytometry, we observed that the more spherical shape of the RBCs in patients with diabetes was not correlated with blood sugar or the severity of the disease as assessed by the HbA 1C . These RBC alterations could increase the risk of peripheral ischaemia in these patients, especially if blood viscosity is increased.…”
Section: Discussionmentioning
confidence: 84%
“…Splenectomy prolongs survival of HS red cells and slows down the decrease in deformability compared to patients that have not undergone splenectomy [20]. The effect of splenectomy is less in HS caused by band 3 deficiency [21].…”
Section: Discussionmentioning
confidence: 99%